2017
DOI: 10.1007/s12036-017-9474-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Distances and Velocities of Neutron Stars

Abstract: Abstract. We take a fresh look at the determination of distances and velocities of neutron stars. The conversion of a parallax measurement into a distance, or distance probability distribution, has led to a debate quite similar to the one involving Cepheids, centering on the question whether priors can be used when discussing a single system. With the example of PSR J0218+4232, we show that a prior is necessary to determine the probability distribution for the distance. The distance of this pulsar implies a ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…At long orbital periods ( 3 h) magnetic braking (Verbunt and Zwaan 1981;Rappaport et al 1983) acts as main mechanism that ceases at ∼3 h when secondaries become fully convective and shrink within their Roche lobe. Mass transfer stops until contact is re-established near ∼2 h. This gives rise to the so-called 2-3 h CV orbital period gap (Rappaport et al 1983;Spruit and Ritter 1983;Davis et al 2008).…”
Section: Evolutionary Aspects Of Magnetic White Dwarf Binariesmentioning
confidence: 99%
“…At long orbital periods ( 3 h) magnetic braking (Verbunt and Zwaan 1981;Rappaport et al 1983) acts as main mechanism that ceases at ∼3 h when secondaries become fully convective and shrink within their Roche lobe. Mass transfer stops until contact is re-established near ∼2 h. This gives rise to the so-called 2-3 h CV orbital period gap (Rappaport et al 1983;Spruit and Ritter 1983;Davis et al 2008).…”
Section: Evolutionary Aspects Of Magnetic White Dwarf Binariesmentioning
confidence: 99%
“…The shape, character, and phasing of the lightcurve are inconsistent with stellar pulsations or ellipsoidal variations, but are typical of the class of spotted K giants like HD 1833, V1192 Orionis, and KU Pegasi (24,25). Such systems in binaries with periods less than ∼ 150 days often have low eccentricities, implying rapid tidal circularization (26)(27)(28). The change in the shape of the lightcurve over time shown in Figure 1 likely indicates spot evolution.…”
mentioning
confidence: 94%
“…Early observations suggested that neutron stars receive natal kicks, and that the velocity is distributed according to a Gaussian with zero mean and a dispersion of about 260 km s −1 (Hobbs et al 2005). Newer observations suggest there might be another population of neutron stars, of which the kick velocities follow a double peaked Gaussian distribution but with smaller dispersions of just 77 km s −1 for 0.42 of the systems and 320 km s −1 for the rest (Verbunt & Cator 2017). Double neutron star binaries exhibit a somewhat similar doubly peaked kick distribution, with roughly two thirds of the systems experiencing kicks lower than 30 km s −1 and others exhibiting larger kicks, consistent with the regular neutron star population (Beniamini & Piran 2016;Tauris et al 2017).…”
Section: Introductionmentioning
confidence: 99%